Toll-Like Receptors in the Progression of Autosomal Dominant Polycystic Kidney Disease - Kocyigit, Ismail; Sener, Elif Funda; Taheri, Serpil; Eroglu, Eray; Ozturk, Fahir; Unal, Aydin; Zararsiz, Gokmen; Uzun, Ilknur; Imamoglu, Hakan; Sipahioglu, Murat Hayri; Tokgoz, Bulent; Oymak, Oktay; et al. (Therapeutic apheresis and dialysis, 2016)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary cause of chronic kidney disease. The intriguing role of innate immune system and inflammation become a target for potential therapeutic approach to slow progression. When toll‐like receptors (TLRs) signaling and their receptors activate, they start a cascade of intracellular signaling that induces the production of the inflammatory cytokines and chemokines. Thus, we aim to investigate the association of TLRs between progression of ADPKD. Ninety ADPKD patients and ninety matched controls were enrolled this prospective study and were followed during 3 years. TLR‐2 and TLR‐4 gene polymorphisms and expressions were measured. Hypertension was diagnosed with ambulatory blood pressure monitoring. Rapid progression was defined as sustained decline in estimated glomerular filtration rate (eGFR) of more than 5 mL/min per 1.73 m2 per year. TLR‐4Asp299Gly polymorphisms were significantly different between patient and control group (P < 0.05). Also, TLR‐2 and TLR‐4 gene expressions were significantly different between the ADPKD patients and the control subjects (P < 0.05). The expression levels of both TLR‐2 and TLR‐4 were found to be higher in the rapid progression groups comparing the slow progression group (P < 0.05). TLR‐2 gene expression, hypertension and uric acid were found to be independent risk factors in identifying rapid progression in ADPKD patients. TLR‐2 and TLR‐4 gene expressions are associated with rapid progression in ADPKD patients. TLRs may play a role in the progression of ADPKD.